Insect pests in okra agro-ecosystem and their integrated management - Krishna, Bal; Kumar, Rakesh; Singh Choudhary, Jaipal; Kumar, Ram; Hans, Hansraj (Indian Horticulture, 2022)
Among vegetable crops, okra has its own importance due to nutritional and medicinal value. In India, West Bengal is the largest producer of okra, followed by Bihar. However, okra production suffers from many biotic and abiotic factors. Among all biotic factors, insect pests are most important as it causes heavy infestation and reduces economic yield. Therefore, it is essential to study about the insect pest life cycle, damage symptom and management practices to control the pest below economic threshold level